Dealing with COVID-19 in Medical Practice: Yet an Uncertain Situation - Shrestha, Prabin (Nepal Journal of Neuroscience, 2021)
COVID-19 pandemic is still uncertain and is going to last longer. The world has learnt a lot to fight against it. However, the world has to learn to live and deal with it in the days ahead. Medical practice has to be innovated and modified to protect medical professionals as well as patients.